Validation of Gene Profiles for Analysis of Regional Lymphatic Metastases in Head and Neck Squamous Cell Carcinoma - Hu, Zhenrong; Yang, Ranran; Li, Li; Mao, Lu; Liu, Shuli; Qiao, Shichong; Ren, Guoxin; Hu, Jingzhou (Frontiers in Molecular Biosciences, 2020)
The progress of Head and Neck Squamous Cell Carcinoma (HNSCC) is dependent on both cancer stem cells (CSCs) and immune suppression. This study was to evaluate the distribution of cancer stem cells and the characteristic immune suppression status in HNSCC primary tumors and lymph nodes. A total of 303 lymph nodes from 25 patients as well as tumor and adjacent normal tissue samples were evaluated by quantitative PCR assay of the markers of CSCs and the characteristic immune suppression. Expressions of selected genes in The Cancer Genome Atlas (TCGA) datasets were also analyzed. In the primary tumors, we found expressions of CSCs markers (ALDH1L1, PECAM1, PROM1) were down-regulated, while immune suppression markers FOXP3, CD47, EGFR, SOX2 and TGFΒ1 were up-regulated significantly when compared with that in adjacent normal tissues. In the lymph nodes, expressions of both CSCs and immune suppression markers were upregulated significantly compared with that in primary tumors. The mRNA expression of selected CSCs and immune suppression markers exhibited the highest expression in the level II of metastasis, then declined in the level III and remained constant at a reduced value in levels IV and V of metastases. These results reveal a comprehensive understanding of the unique genetic characteristics associated with metastatic loci and potential routes of lymphatic dissemination of HNSCC, which helps to explain why the level II has a high incidence of lymph node metastasis, and why skip metastasis to the level IV or level V is rarely found in the clinic.